2022
DOI: 10.3389/fenrg.2022.900449
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Multidimensional Energy Poverty and Its Economic Impact on N11 Countries: Mediating Role of Energy Efficiency

Abstract: This study seeks to estimate energy poverty using a multidimensional and wide-ranging category of indicators via the GRA-SRA approach. The study entails a case study analysis of the N-11 nations utilizing data from 2000 to 2017. Thus, a formulation of multidimensional energy poverty indexes of multidimensional indicators crosswise three dimensions is carried out. Energy availability, energy affordability, and energy cleanability, with regard to the N11 nations, are taken into account. The findings reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Energy inequality has become a significant research topic due to its social, economic, and environmental implications. Researchers from a wide range of disciplines, including social sciences, economics, public policy, and even engineering, are now exploring different aspects of energy inequality, such as the factors that contribute to energy inequality, the economic and social impacts of energy inequality [8][9][10][11][12][13][14][15], the impact on health [13,[16][17][18][19][20][21][22][23], the impact on vulnerable members of the society [24][25][26][27][28][29], the impact on environmental quality [30][31][32][33][34][35][36], and the policies and strategies that can help to promote energy access and equity. Recent advancements in data collection and analysis have also enabled researchers to better understand the magnitude and distribution of energy inequality across different regions and populations.…”
Section: The Conceptmentioning
confidence: 99%
See 4 more Smart Citations
“…Energy inequality has become a significant research topic due to its social, economic, and environmental implications. Researchers from a wide range of disciplines, including social sciences, economics, public policy, and even engineering, are now exploring different aspects of energy inequality, such as the factors that contribute to energy inequality, the economic and social impacts of energy inequality [8][9][10][11][12][13][14][15], the impact on health [13,[16][17][18][19][20][21][22][23], the impact on vulnerable members of the society [24][25][26][27][28][29], the impact on environmental quality [30][31][32][33][34][35][36], and the policies and strategies that can help to promote energy access and equity. Recent advancements in data collection and analysis have also enabled researchers to better understand the magnitude and distribution of energy inequality across different regions and populations.…”
Section: The Conceptmentioning
confidence: 99%
“…This systematic literature review has identified that various terms are used to address similar aspects of energy inequality (see Figure 1) [17], including energy poverty [9,14,18,20,21,26,32,37], energy insecurity [17,38], fuel poverty [39][40][41][42][43], environmental inequality [34], carbon inequality [44], and environmental degradation [13,31,36]. To achieve the objective of this study, which is to identify energy inequality dimensions and their indicators and explore ways to reduce them, it is crucial to establish a common understanding and terminology.…”
Section: The Conceptmentioning
confidence: 99%
See 3 more Smart Citations